Biochemical characterization and low-resolution SAXS structure of an exo-polygalacturonase from Bacillus licheniformis - Evangelista, Danilo Elton; de Araújo, Evandro A.; Neto, Mario Oliveira [UNESP]; Kadowaki, Marco Antonio Seiki; Polikarpov, Igor (Elsevier, 2018)
Among the structural polymers present in the plant cell wall, pectin is the main component of the middle lamella. This heterogeneous polysaccharide has an α-1,4 galacturonic acid backbone, which can be broken by the enzymatic action of pectinases, such as exo-polygalacturonases, that sequentially cleave pectin from the non-reducing ends, releasing mono or di-galacturonic acid residues. Constant demand for pectinases that better suit industrial requirements has motivated identification and characterization of novel enzymes from diverse sources. Bacillus licheniformis has been used as an important source for bioprospection of several industrial biomolecules, such as surfactants and enzymes, including pectate lyases. Here we cloned, expressed, purified, and biochemically and structurally characterized an exo-polygalacturonase from B. licheniformis (BlExoPG). Its low-resolution molecular envelope was derived from experimental small-angle scattering data (SAXS). Our experimental data revealed that BlExoPG is a monomeric enzyme with optimum pH at 6.5 and optimal temperature of approximately 60 °C, at which it has considerable stability over the broad pH range from 5 to 10. After incubation of the enzyme for 30 min at pH ranging from 5 to 10, no significant loss of the original enzyme activity was observed. Furthermore, the enzyme maintained residual activity of greater than 80% at 50 °C after 15 h of incubation. BlExoPG is more active against polygalacturonic acid as compared to methylated pectin, liberating mono galacturonic acid as a unique product. Its enzymatic parameters are Vmax = 4.18 μM.s−1, Km = 3.25 mgmL−1 and kcat = 2.58 s−1.
Keywords: Biochemical characterization; Exo-polygalacturonase; Pectinase; SAXS molecular envelope; Thermal and pH stability